Standard Agreements and Legal Protection Customers of Financial Service Institutions - Jonker Sihombing (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
In carrying out its business activities, Financial Services Institutions carry out civil legal relations with the parties, and this is formalized in the form of a written agreement. This research analyzes how regulations are regulated in statutory regulations regarding standard agreements between customers and Financial Services Institutions and the extent of legal protection for customers of the Financial Services Institutions in question. The research carried out is normative juridical, using secondary data consisting of primary legal materials in the form of statutory regulations, supported by secondary legal materials in the form of books, literature, and legal journals. The research results show that the use of standard agreements is a common practice for Financial Services Institutions today. Not only is the standard agreement design formatted according to the interests of the Financial Services Institution as the more dominant party in the agreement, but it also contains extenuating clauses that burden other parties in the agreement. From the research results, it was concluded that customers' rights were more disadvantaged due to standard agreements made by Financial Services Institutions. In addition, standard agreements that contain exemption clauses give rise to legal consequences for customers, namely that the responsibility that should be borne by the Financial Services Institution changes to become the responsibility of the customer.